2020
DOI: 10.1016/j.hlc.2020.05.004
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 – Does This Disease Kill Due to Imbalance of the Renin Angiotensin System (RAS) Caused by Genetic and Gender Differences in the Response to Viral ACE 2 Attack?

Abstract: Debate continues in the medical literature on the role of the renin angiotensin system (RAS) in Coronavirus disease 2019 (COVID-19) pathophysiology and the implications for the use of cardiovascular drugs acting on the RAS. Could these drugswhich include angiotensin converting enzyme inhibitors (ACEIs) and angiotensin receptors blockers (ARBs)be harmful or potential key therapeutic agents in COVID-19? And, could potentially helpful measures be available and in plain view on the pharmacy shelf? KeywordsCOVID 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 51 publications
0
41
0
Order By: Relevance
“…After further exclusion for non-Covid related, not relevant and only protocols, 59 publications were reviewed ( Supplementary Table S1). Twenty five (8 observational, 4 ecological, 1 interventional non-RCT, 4 Systematic review/meta-analysis/review and 8 editorial) new studies specifically explored the role of vitamin D deficiency in the progression of ARDS in COVID-19 infection (Arnold, 2020;Aygun, 2020;Brenner et al, 2020;Chakhtoura et al, 2020;D'Avolio et al, 2020;Ebadi and Montano-Loza, 2020;Faul et al, 2020;Haj Bloukh et al, 2020;Hastie et al, 2020;Ilie et al, 2020;Laird et al, 2020;Martineau and Forouhi, 2020;Meltzer et al, 2020;Ohaegbulam et al, 2020;Panagiotou et al, 2020;Quesada-Gomez et al, 2020; Raisi-Estabragh et al, 2020; Silberstein, 2020; Singh et al, 2020;Slominski et al, 2020;Sun et al, 2020;Townsend et al, 2020;Tramontana et al, 2020;Whittemore, 2020) (Tables 2, 3). Figure 2 presents a PRISMA diagram of the review search B.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After further exclusion for non-Covid related, not relevant and only protocols, 59 publications were reviewed ( Supplementary Table S1). Twenty five (8 observational, 4 ecological, 1 interventional non-RCT, 4 Systematic review/meta-analysis/review and 8 editorial) new studies specifically explored the role of vitamin D deficiency in the progression of ARDS in COVID-19 infection (Arnold, 2020;Aygun, 2020;Brenner et al, 2020;Chakhtoura et al, 2020;D'Avolio et al, 2020;Ebadi and Montano-Loza, 2020;Faul et al, 2020;Haj Bloukh et al, 2020;Hastie et al, 2020;Ilie et al, 2020;Laird et al, 2020;Martineau and Forouhi, 2020;Meltzer et al, 2020;Ohaegbulam et al, 2020;Panagiotou et al, 2020;Quesada-Gomez et al, 2020; Raisi-Estabragh et al, 2020; Silberstein, 2020; Singh et al, 2020;Slominski et al, 2020;Sun et al, 2020;Townsend et al, 2020;Tramontana et al, 2020;Whittemore, 2020) (Tables 2, 3). Figure 2 presents a PRISMA diagram of the review search B.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, our literature review identified a number of studies/reviews (n = 24) providing some insight into the mechanistic explanations for the observed epidemiological relationship between vitamin D deficiency and increased risk/severity of respiratory infections (Ginde et al, 2009;Laaksi, 2012;Pfeffer and Hawrylowicz, 2012;He et al, 2013;Parekh et al, 2013;Lambert et al, 2014;Dancer et al, 2015;Greiller and Martineau, 2015;Vargas Buonfiglio et al, 2017;Xu et al, 2017;Jolliffe et al, 2018;Miraglia Del Giudice et al, 2018;Iyer and Bansal, 2019;Aygun, 2020;Brenner et al, 2020;Carter et al, 2020;Jakovac, 2020;Kakodkar et al, 2020;Maes et al, 2020;McCartney and Byrne, 2020;Misra et al, 2020;Molloy and Murphy, 2020;Panarese and Shahini, 2020;Quesada-Gomez et al, 2020;Tian and Rong, 2020;Zheng et al, 2020). Studies and narrative reviews suggest that entry of SARS-CoV-2 infection into alveolar epithelial cells, triggered by binding of the virus surface spike (S)-protein to the angiotensin converting enzyme 2 (ACE2) receptor, may lead to dysregulation of the renin-angiotensin system (RAS) resulting in acute lung injury due to toxic overaccumulation of angiotensin II (Ang II) in alveolar cells (Pfeffer and Hawrylowicz, 2012;Arnold, 2020;Carter et al, 2020;Jakovac, 2020;Kakodkar et al, 2020;Misra et al, 2020;Panarese and Shahini, 2020;Tian and Rong, 2020). Evidence suggests that vitamin D deficie...…”
Section: Resultsmentioning
confidence: 99%
“…56 Likewise, increased serum Ang II levels correlating to viral load and lung injury have been observed in individuals with COVID-19. 55 Children (<10 years) were found to have lower ACE-2 expression (2.4 mean log 2 , counts per million) in the nasal epithelium, one of the main points of entry of SARS-CoV-2. A marked increase with mean log 2 counts per million of 2.77 and 3.02 were seen in older children and young adults, respectively, which may explain the lower incidence of COVID-19 in the younger age group.…”
Section: Postulated Mechanisms For the Age-dependent Differences In Imentioning
confidence: 98%
“…In COVID-19, binding of SARS-CoV and SARS-CoV-2 virus to cell surface ACE-2 receptors allows viral entry and downregulates ACE-2 expression. 55 This results in reduced protection against lung injury and upregulation of the proinflammatory Ang II pathway, manifesting as increased disease severity. 56 Likewise, increased serum Ang II levels correlating to viral load and lung injury have been observed in individuals with COVID-19.…”
Section: Postulated Mechanisms For the Age-dependent Differences In Imentioning
confidence: 99%
“…SARS-CoV-2 was quickly determined to infect host cells via angiotensin converting enzyme 2 (ACE 2) receptors; initial concern about the safety and efficacy of continued use of ACE-inhibitors and angiotensin receptor blockers in patients being treated for hypertension or heart failure has given way to sustained interest in a possible role of the renin-angiotensin system (RAS) in the pathophysiology of COVID-19. Arnold was among the first to raise the possibility that an imbalance of the RAS, related to genetic and genetic differences in the response to a viral ACE attack, may be linked to the clinical severity of COVID-19 [4]. Kasal et al have since contributed an elegant review of microvascular dysfunction in COVID-19, and renewed interest in the RAS-reminding us that it is "a powerful homeostatic system developed hundreds of millions of years ago, allowing salt and water retention essential for vertebrates once they left their original marine environment" [5,6].…”
Section: Acute Cardiovascular Issuesmentioning
confidence: 99%